Analysis of Changes in the Stress-Strain State and Permeability of a Terrigenous Reservoir Based on a Numerical Model of the Near-Well Zone With Casing and Perforation Channels - S. E. Chernyshov; S. N. Popov; X. Wang; V. V. Derendyaev; Y. Yang; H. Liu (Georesursy, 2024)
A finite-element scheme has been developed, including a section of reservoir rock, cement stone, casing and perforation channels. It is noted that in order to exclude the occurrence of stress concentrators at the casing – cement stone and cement stone – rock contacts, contact elements are specified in the numerical model, due to this, structural elements «slip», but at the same time, a reliable redistribution of stresses is carried out. Numerical simulation of the stress state of the near-wellbore zone using the developed model with varying depression on terrigenous reservoir for the conditions of one of the Perm Region oil field is carried out. It is shown that the safety factor of the casing is about 3–4 units, with the exception of small areas near the upper and lower areas of the perforations, where this indicator is close to one. For cement stone, the safety factor was 2-3 units and however, areas with its lowest value (1.35), also concentrated near the perforation channels, were note. To analyze the change in permeability, the dependence of this characteristic on effective stresses was used and it was found that zones of reduced stresses and an increase in permeability up to 20% of the initial value are detected in the upper and lower parts of the perforations. With an increase in depression on the reservoir, permeability decreases, especially in the lateral sections of the holes, where this parameter can decrease by 25% of the initial value. Using the Coulomb-Mohr criterion, areas of rock destruction from stretching and compression were identified. It is noted that with increasing depression, the areas of destruction under tensile stresses disappear and the areas of destruction under compression increase. An analysis of the change in the productivity coefficient depending on the depression showed that when creating a maximum depression on the 12 MPa formation, the productivity coefficient of the well can decrease by 15% due to compaction of the reservoir rock caused by an increase in effective stresses.